Placenta percreta with bladder invasion – a novel approach for management: A case report - Sushila Kharkwal; Divya Jain; Manish Jain; Shitangsu Kakoti; Divya Pandey (Asian Journal of Medical Sciences, 2022)
Placenta percreta is an obstetric emergency often associated with massive hemorrhage, emergency cesarean section, and peripartum hysterectomy. We present a case of a 30-year-old woman, G4P1L1A2 with placenta percreta managed by an alternative approach. The placenta was left in situ along with B/L internal iliac artery ligation during cesarean section and later on delayed subtotal hysterectomy with bladder repair was successfully performed. Placenta percreta spectrum is an obstetricians dilemma associated with massive hemorrhage and is a potential life-threatening condition for both mother and the baby. Cesarean section with B/L internal iliac artery ligation and delayed hysterectomy may be a reasonable strategy in the most severe cases.